Life-trajectory and identity in the cases of Helena Almeida and Jorge Molder = Trajetórias de vida e identidade em Helena Almeida e Jorge Molder - Anabela Pereira (Análise Social, 2013)
Life-trajectory and identity in the cases of Helena Almeida and Jorge Molder. The aim of this article is to enhance the role of the practices of self-representation in Helena Almeida and Jorge Molder as a constituent of artist’s identity construction processes using a Multiple Correspondence Analysis (mca). It also emphasizes the idea of self-representation as the result of their embodied experiences as well as of the forms of acknowledgment and legitimization of their names.